An insight into the development of the royalty definition contained in modern model tax conventions and the evolution of the international tax meaning of 'beneficial ownership' - Greyling, Johannes Barend (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm) -- Stellenbosch University, 2011.